Cropping system management for mitigation of second-generation problems in agriculture - Gangwar, B G; Prasad, Kamta (The Indian Journal of Agricultural Sciences, 2005)
Widespread occurrence of second-generation problems, such as over-mining of soil nutrients, decline in factor productivity, reduction in profitability, lowering of groundwater tables and build up of pests including weeds, diseases and insects has been reported during post-green revolution era in most of the intensively cultivated, high-productivity, cerealbased production systems, which are threatening their sustainability. The research results during the last 2 decades have clearly established that these adverse impacts of green revolution technologies may be mitigated through an appropriate choice of alternative crops and cropping systems, which are efficient user of resource base (land, water, light and energy), economically more remunerative and environment-friendly. An adoption of well-designed situation-specific alternative cropping systems along with appropriate method of cultivation could minimize the occurrence or intensity of diseases and insect pests, including weeds, considerably. These are also helpful in conservation of the soil resource, improvement of soil health and protection of the environment by minimizing nitrate leaching, besides improving nutrient and water-use efficiencies. System-based integrated nutrient management, integrated pest management and resource conservation technologies such as, zero tillage, furrow-irrigated raised bed, and ridge or bed planting are some of the new technologies deserving immediate focus. The suggested strategies of immediate concern are complementary intensive intercropping systems under limited water availability, quantification of on-farm impacts of diversification options on productivity, stability, profitability, soil health, water and nutrient-use productivity development of sustainable production models using computer software, organic farming systems, focus on system-based integrated resource management, development of site-specific precision input management and resource-conservation Technologies, appropriate policies for multi-disciplinary research through inter-institutional and or inter-organizational collaborative programmes, and development of appropriate decision-support systems for'diversification options and resource-use optimization under variable scenarios.